Lipor´s crew project - a case for the relevance of impact measurement and implications for the successful execution of project endeavours related to the UN´s sustainable development goals in the public sector - Stuelb, Gideon (2022)
This case study explains the concrete steps the project management of the CREW project, a partnership of Lip or and ERP Portugal, took to manage the project from 2019 to2020. The corresponding teaching note demonstrates the relevance of measuring impact, discusses several impact assessment frameworks and finally picks the Social Return on Investment (SROI). The application of the SROI framework is outlined, and learnings are generalized. In the project evaluation report, an SROI analysis is executed for CREW. Based on this, targeted recommendations and implementation plans are provided, including a detailed work breakdown structure and monitoring and risk management remarks.